2014
DOI: 10.4068/cmj.2014.50.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Epidemiology, Treatment, and Outcomes of Carbapenem-resistantAcinetobacter infections

Abstract: Carbapenem-resistant Acinetobacter species are increasingly recognized as major nosocomial pathogens, especially in patients with critical illnesses or in intensive care. The ability of these organisms to accumulate diverse mechanisms of resistance limits the available therapeutic agents, makes the infection difficult to treat, and is associated with a greater risk of death. In this review, we provide an update on the epidemiology, resistance mechanisms, infection control measures, treatment, and outcomes of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 71 publications
1
56
1
9
Order By: Relevance
“…baumannii is an emerging pathogen commonly found in hospitalized patients, especially those in ICU wards (Kim et al, 2014). Countrywide reports of outbreaks of MDR strains have increased in the past few years in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…baumannii is an emerging pathogen commonly found in hospitalized patients, especially those in ICU wards (Kim et al, 2014). Countrywide reports of outbreaks of MDR strains have increased in the past few years in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, carbapenem-resistant P. aeruginosa isolates from the United States collected in 2010 as part of the Carbapenem Antimicrobials Pseudomonas Isolate Testing at regional Locations (CAPITAL) study demonstrated the highest rates in the southern United States, with 35%, 26%, and 19% resistance to imipenem, meropenem, and doripenem, respectively (12). These increases in carbapenem resistance among non-glucose-fermenting Gram-nega-tive bacilli can be attributed to multiple factors, such as the increased use of broad-spectrum antibiotics (including the carbapenems), the use of indwelling medical devices, an increase in immunocompromised host populations, and the acquisition of carbapenemases (4,5). Notably, the highest burden of carbapenem resistance among Gram-negative health care-associated infections in the United States, as reported by the NHSN from 2009 to 2010, was observed among A. baumannii (62.6%) and P. aeruginosa (26.1%) in comparison to CRE, in which carbapenem resistance was highest among Klebsiella pneumoniae, at 12.8%.…”
Section: Epidemiology Of Cr-nfmentioning
confidence: 99%
“…The rates of carbapenem resistance in non-glucose-fermenting Gram-negative bacilli have been gradually increasing worldwide over the last 10 years and vary geographically (4,5). Recent studies from South Korea have reported the proportion of carbapenem resistance in Acinetobacter to be as high as 32 to 56% in hospitalized patients (6,7).…”
Section: Epidemiology Of Cr-nfmentioning
confidence: 99%
“…NFGNB do not require many nutrients for their development, can tolerate harsh environmental conditions, show remarkable resistance to antimicrobials, and are frequently described as hospital-acquired opportunistic pathogens [2][3][4] . Multidrug resistance of NFGNB stems from different factors, such as up-regulated production of enzymes metabolizing the drugs, target site changes, overexpression of efflux pumps, and porin deficiency 5,6 . Metallobeta-lactamase (MBL) production, mainly by Pseudomonas aeruginosa, stands out as a frequent cause of severe nosocomial infections 7,8 .…”
mentioning
confidence: 99%